2015
DOI: 10.1002/eqe.2574
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐plane strength reduction of unreinforced masonry walls because of in‐plane damages

Abstract: Summary There are numerous studies on the behavior of Unreinforced Masonry (URM) walls in both in‐plane (IP) and out‐of‐plane (OP) directions; however, few aimed at understanding the simultaneous contribution of these intrinsic responses during earthquakes. Undoubtedly, even a strong URM wall shows weakened capacity in the OP direction because of minor cracks and other damages in the IP direction, and this capacity reduction has not yet been accounted for in seismic codes. In this study, performance of three U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Another way of presenting IP-OP interaction for the models in this study is in the form of normalized OP strength versus IP drift ratio. These results for Model-1 and Model-2 together with the results proposed by Dolatshahi and Yekrangnia [25] are shown in Fig. 20.…”
Section: Results Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Another way of presenting IP-OP interaction for the models in this study is in the form of normalized OP strength versus IP drift ratio. These results for Model-1 and Model-2 together with the results proposed by Dolatshahi and Yekrangnia [25] are shown in Fig. 20.…”
Section: Results Discussionsupporting
confidence: 64%
“…It was shown that regardless of the aspect ratio and existence of vertical loads, the OP behavior of infilled frames is not noticeably affected by the IP displacement demand, provided that the displacement is smaller than the displacement related to IP ultimate strength. Unlike the unreinforced masonry walls in which they experience considerable reduction in the OP strength capacity even by applying a small IP displacement [24,25], masonry infill walls benefit from the positive effects of formation of IP diagonal compressive struts in improving the arching action as well as in increasing their OP strength capacity. This is an interesting finding in this study since it clearly proves that the IP and OP interaction for masonry infilled frames may not be much of concern and therefore, the available relations in the design codes for determination of the IP and OP strength capacity of infilled frames as independent behaviors can lead to accurate results.…”
Section: Discussionmentioning
confidence: 99%
“…In slender façades, the dynamic interaction between in‐plane and out‐of‐plane movements tends to be scarce, because the in‐plane vibration modes correspond to periods that are usually much shorter than the flexural ones. On the other hand, a much more complex interaction between in‐plane and out‐of‐plane damage mechanisms can be expected in very different façade typologies, such as some baroque façades, which are not simply planar and often integrate heavy bell towers …”
Section: Discrete Models Of the Masonry Façadesmentioning
confidence: 99%
“…15,17 The main façades are on the left side of the drawings a much more complex interaction between in-plane and out-of-plane damage mechanisms can be expected in very different façade typologies, such as some baroque façades, which are not simply planar and often integrate heavy bell towers. [25][26][27][28] For the purposes of the present study, the numerical modelling should be efficient, to perform full nonlinear dynamic analyses with an acceptable computational effort, but not simplistic, since the damage response of the building materials, in the context of the composite nature of the 3-leaf masonry walls, should be properly included. [29][30][31][32] Special attention should be devoted to the definition of a reasonable nonlinear material response compatible with the experimental evidence as well as with analytical and microstructure numerical modelling, 16,33,34 by accounting for the static vertical compression, the 3-leaf bond effects, the internal friction, and the progression of damage with hysteretic dissipation.…”
Section: Out-of-plane Damage Mechanismsmentioning
confidence: 99%
“…Examination of the literature also reveals that most of the studies have focused on two‐dimensional behavior of URM walls. An extensive review by Dolatshahi of existing technical literature shows that there are few material models equipped to simulate the three‐dimensional behavior of URM walls . The authors have developed a three‐dimensional numerical procedure for modeling URM walls .…”
Section: Introductionmentioning
confidence: 99%